Long-Term Supplementation of Green Tea Extract Does Not Modify Adiposity or Bone Mineral Density in a Randomized Trial of Overweight and Obese Postmenopausal Women. Issue 2 (23rd December 2015) - Dostal, Allison M; Arikawa, Andrea; Espejo, Luis; Kurzer, Mindy S
Abstract: Background: Green tea extract (GTE) consumption has been linked to favorable changes in adiposity and bone mineral density (BMD), although it is unknown if these effects are due to green tea catechins or caffeine. The catechol- O -methyltransferase ( COMT ) genotype may also modify these associations. Objective: We examined the impact of decaffeinated GTE on body composition (using dual-energy X-ray absorptiometry) and obesity-associated hormones. Methods: The Minnesota Green Tea Trial was a 12-mo randomized, double-blind, placebo-controlled clinical trial in 937 postmenopausal women (aged 50–70 y) assigned to receive either GTE containing 843 mg (−)-epigallocatechin-3-gallate or placebo. This substudy was conducted in 121 overweight/obese participants [body mass index (BMI) (kg/m 2 ) ≥25.0]. Results: There were no differences in changes in BMI (−0.13 ± 0.11 compared with −0.05 ± 0.11; P = 0.61), total fat mass (−0.30 ± 0.16 compared with −0.12 ± 0.15 kg; P = 0.40), percentage of body fat (−0.15% ± 0.17% compared with −0.15% ± 0.16%; P = 0.99), or BMD (−0.006 ± 0.002 compared with −0.003 ± 0.002 g/cm 2 ; P = 0.49) over 12 mo between women taking GTE ( n = 61) and those taking a placebo ( n = 60). Interactions were observed between treatment and time for gynoid percentage of fat (%fat) and tissue %fat. Gynoid %fat increased from baseline to month 12 in the placebo group as baseline BMI increased and decreased over time as baseline BMI increased in the GTE group ( P- interaction = 0.02). Tissue %fat increased from baseline to month 12 in the placebo group as baseline BMI increased. In the GTE group, tissue %fat decreased during the intervention as baseline BMI increased ( P- interaction = 0.04). No changes were seen in circulating leptin, ghrelin, adiponectin, or insulin concentrations. COMT genotype did not modify the effect of GTE on any variable. Conclusions: Decaffeinated GTE was not associated with overall reductions in adiposity or improvements in BMD in overweight/obese postmenopausal women. However, GTE may be beneficial for reduction in tissue and gynoid %fat in individuals with higher BMI. This clinical trial was registered at www.clinicaltrials.gov as NCT00917735.